Deferoxamine attenuates lipopolysaccharide-induced neuroinflammation and memory impairment in mice - Zhang, Xiao-Ying; Cao, Jiang-Bei; Zhang, Li-Ming; Li, Yun-Feng; Mi, Wei-Dong (Journal of neuroinflammation, 2015)
Background Neuroinflammation often results in enduring cognitive impairment and is a risk factor for postoperative cognitive dysfunction. There are currently no effective treatments for infection-induced cognitive impairment. Previous studies have shown that the iron chelator deferoxamine (DFO) can increase the resistance of neurons to injury and disease by stimulating adaptive cellular stress responses. However, the impact of DFO on the cognitive sequelae of neuroinflammation is unknown. Methods A mouse model of lipopolysaccharide (LPS)-induced cognitive impairment was established to evaluate the neuroprotective effects of DFO against LPS-induced memory deficits and neuroinflammation. Adult C57BL/6 mice were treated with 0.5 μg of DFO 3 days prior to intracerebroventricular microinjection of 2 μg of LPS. Cognitive function was assessed using a Morris water maze from post-injection days 1 to 3. Animal behavioral tests, as well as pathological and biochemical assays were performed to evaluate the LPS-induced hippocampal damage and the neuroprotective effect of DFO. Results Treatment of mice with LPS resulted in deficits in cognitive performance in the Morris water maze without changing locomotor activity, which were ameliorated by pretreatment with DFO. DFO prevented LPS-induced microglial activation and elevations of IL-1β and TNF-α levels in the hippocampus. Moreover, DFO attenuated elevated expression of caspase-3, modulated GSK3β activity, and prevented LPS-induced increases of MDA and SOD levels in the hippocampus. DFO also significantly blocked LPS-induced iron accumulation and altered expression of proteins related to iron metabolism in the hippocampus. Conclusions Our results suggest that DFO may possess a neuroprotective effect against LPS-induced neuroinflammation and cognitive deficits via mechanisms involving maintenance of less brain iron, prevention of neuroinflammation, and alleviation of oxidative stress and apoptosis.